1988
DOI: 10.1038/ki.1988.192
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators in patients presenting with the nephrotic syndrome

Abstract: Clinical data from 246 patients presenting with a nephrotic syndrome and biopsy-proven glomerular disorder were analyzed, using statistical survival techniques, to determine which of several variables (sex, age, plasma creatinine, diastolic blood pressure and 24-hour urinary protein loss) were associated with subsequent end-stage renal failure. The best prediction of outcome could be made at one year (N = 121); then plasma creatinine (P less than 0.001) and heavy proteinuria (P = 0.049) were the best determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Nevertheless, there was a significant reduction in the number of patients having a 50% reduction in creatinine clearance over time in the low protein diet group (28.6%) compared to the control diet group (40%; p =0.038). In addition the initial level of proteinuria was shown to be an independent risk factor for progression of renal failure, as also reported by other investigators (22,23).…”
Section: Non-diabetic Renal Failuresupporting
confidence: 82%
“…Nevertheless, there was a significant reduction in the number of patients having a 50% reduction in creatinine clearance over time in the low protein diet group (28.6%) compared to the control diet group (40%; p =0.038). In addition the initial level of proteinuria was shown to be an independent risk factor for progression of renal failure, as also reported by other investigators (22,23).…”
Section: Non-diabetic Renal Failuresupporting
confidence: 82%
“…As is well known, the emergence of urinary microalbumin is a necessary indicator for the diagnosis of DN, and urinary albumin increase is an important indicator of the deterioration of DN. 22 Studies have shown that in patients with type 2 diabetes, 24-hour urinary protein (urinary albumin excretion rate) ≥30 mg/24 hours increased the risk of cardiovascular events, DN, and death by 2.20 times, 6.76 times, and 2.47 times. 23 Therefore, for the treatment of DN, it is important to reduce urinary protein excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis using the fixed-effects model was repeated using four studies (7,10,12,13) that contained 1664 patients, after exclusion of four studies that used an outcome measure other than ESRD requiring renal replacement therapy or a decline in isotopically determined GFR. Excluded studies used a rise in serum creatinine (n ϭ 3) or a decline in creatinine clearance (n ϭ 1) as an outcome measure.…”
Section: Chronic Renal Diseasementioning
confidence: 99%